Strategi Bertahan Home Industry Kopyah Abu Imam Pasuruan - Yudowati, Dewi Mumpuni; Ningsih, Unia (Lembaga Pusat Penelitian dan Pengabdian kepada Masyarakat (LP2M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
Competition in the business world is unavoidable, therefore if you want to enter the business world, you need self-preparation or a survival strategy to face other business competitors. Survival strategies are several ways that are used by a person, or group of people to maintain the existence of a self that is valuable or considered valuable, both material and non-material.The approach used in this study is a qualitative approach. Qualitative research is research that aims to gain a deep understanding of a phenomenon in a society without using the process of measurement and calculation. Data collection methods used in this study include observation or observations, interviews with key informants, and documentation that supports the research process. The data analysis technique used in this research is using SWOT analysis.Based on the results of the analysis, it can be seen that the best defensive strategy that must be done at this time is to apply the SO (strength opportunities) strategy. This strategy is carried out to take advantage of the company's strengths in order to capture the opportunities the company has. Using promotional media that is right on target, namely promotional media with internet networks because promotional media with internet networks are very appropriate to use in the modern era, consumers can access their requests easily and flexibly because they can be done anywhere and anytime. The researcher hopes that entrepreneurs will pay more attention to the problems of competition and obstacles in the home industry so that they can compete with large industries. Keyword: Defensive Strategy, SWOT Analysis